Special events during the launch of unmanned aerial vehicles for the protection of public order (Journal of actual problems of jurisprudence, 2022)
The research work consists in determining the relations arising in public relations by differentiating the legal norms reflected in the legislation of the Republic of Kazakhstan during the analysis of measures taken to protect public order when launching unmanned aerial vehicles. One of the necessary problems is to identify actions that harm the lives of people, citizens and the state on the basis of events taking place in modern public life. Due to the insufficiency of regulatory norms in regulatory legal acts regulating the rights and freedoms of man and citizens, the study suggests measures to improve the current legislation.The shortcomings and gaps in the legal regulation of the use of unmanned aerial vehicles (using the example of quadrocopters, drones) used for operational photo and video filming of site inspection on the example of incidents in the internal affairs bodies are revealed. Possible difficulties of their use in the airspace near airports and other strategically important facilities have been identified.Therefore, when writing a research paper, general and special methods and techniques were used. The offense, which is an encroachment on privacy, is currently multiple in nature through video recording.Keywords: unmanned aircraft, quadrocopters, air space, a threat to security, public interests.